2015
DOI: 10.1080/13548506.2015.1032309
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of Chinese primary care patients with lower urinary tract symptoms

Abstract: The aim of this study was to evaluate the mental health of Chinese primary care patients with lower urinary tract symptoms (LUTS). This was a cross-sectional observational study. Five hundred and nineteen subjects with LUTS completed a structured questionnaire containing the Depression, Anxiety, and Stress Scale-Short Form, the International Prostate Symptom Score, the adapted International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form and questions about socio-demographics. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…High scores suggest that the symptomatology is severe. The recommended cut-offs points for each subscale are as follows: depression [normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (28+)], anxiety [normal (0-7), mild (8-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (20+)], and stress [normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33), and extremely severe (34+)] [14,…”
Section: Methodsmentioning
confidence: 99%
“…High scores suggest that the symptomatology is severe. The recommended cut-offs points for each subscale are as follows: depression [normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (28+)], anxiety [normal (0-7), mild (8-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (20+)], and stress [normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33), and extremely severe (34+)] [14,…”
Section: Methodsmentioning
confidence: 99%
“…The expected embarrassment and the possible threat to masculinity caused by disclosing one's urinary symptoms and their associated problems, especially erectile dysfunction (ED) problems, might also account for their silence. Previous research has highlighted the importance of self-management strategies and interventions to improve the quality of life of people with urinary problems [26,55]. However, from a psychological perspective, related education workshops and campaigns to reduce the potential maladaptive cognitive beliefs about urinary problems and their symptoms are needed in order to promote help-seeking behaviours and early treatment for urinary problems [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of Chinese men aged 62-92 in Hong Kong, using the Geriatric Depression Scale [19], the study found that nearly two-thirds (64.7%) of men who had "moderate to severe" LUTS were also depressed. Studies on the relationship between urinary problems and mental health issues in Chinese men in Hong Kong are few in number [26,27] and there is a need to better understand the impact of urinary problems on general psychological functioning in Hong Kong men. This study is one of the only few studies that has focused on general mental health status and distress in a sample of Chinese men.…”
Section: Introductionmentioning
confidence: 99%
“…, ) and mental health (Choi et al . ). The global prevalence of LUTS was reported to be 45·2% in both males and females in 2008 (Irwin et al .…”
Section: Introductionmentioning
confidence: 97%
“…Lower urinary tract symptoms (LUTS) are a leading cause of burden to health-related quality of life (HRQOL) (Choi et al 2014a(Choi et al , 2016a and mental health (Choi et al 2016b). The global prevalence of LUTS was reported to be 45Á2% in both males and females in 2008 (Irwin et al 2011) and it is estimated that by 2018, 2Á3 billion people worldwide will have LUTS (Irwin et al 2011).…”
Section: Introductionmentioning
confidence: 99%